Indonesian Teachers’ Perceptions of Students’ Problems and The Possible Causes when Speaking English in The EFL Classroom - Anisatul Maysaroh; Siti Masrifatul Fitriyah; Bambang Suharjito (EFL Education Journal, 2022)
English Speaking skill plays an important role in communication for EFL learners, including those in Indonesia. However, the problem of speaking English is a frequently encountered topic of discussion in the body of literature and in educational contexts. There are various problems that are listed as the possible causes of language learners’ incompetence in speaking English from teachers’ perceptions which have to be investigated. In order to examine the teachers’ perceptions of students’ problems and possible causes when speaking English in the EFL classrooms, I interviewed three English teachers in a junior high school. Semi structured-interview was used to generate data, which were then analysed by using the Interactive Model of data analysis. The results indicated that lack of vocabulary, lack of confidence, fear of making mistakes and language anxiety as students’ problems in speaking. In addition, the teachers perceived the possible causes derived from both intrinsic and extrinsic factors such as students’ motivation or willingness to practice speaking English and the environmental factors like family support which hindered the students from delivering their best speaking performance.